Possible Association of CD68 Positive Macrophages with Some other Prognostic Factors (ki67, ER, PR, Her2 neu) in Primary Breast Cancer and Axillary Lymph Node Metastasis - Hakime Khalili; Shahriar Dabiri; Bahram Pourseyedi; Hamid Zeinalinejad (Journal of Kerman University of Medical Sciences, 2017)
Background: Breast cancer is formed of a neoplastic component (epithelial) and a non-neoplastic component (stroma). Stromal- stromal and tumor- stromal interactions have been shown in the regulation of cancer cell growth, metastatic capacity and outcome of treatment. Tumor-associated macrophages (TAMs) are a component of tumor stroma reactionsand are considered as an important component of breast cancer tumor tissue which approximately form 50 % to 80 % of tumor tissue.In this study, the frequency of CD68 positive cells in association with other factors such as age, tumor size, ER, PR, Ki-67, Her2-neu receptors, stage and grade in invasive carcinoma tissues were morphologically and statistically evaluated. The frequency of CD68 was also discussed in relation to the number of involved lymph nodes. Method: A total of 50 invasive breast cancer patients with and without axillary lymph nodes involvement were studied. IHC staining for CD68 and Ki-67 markers was performed. For each tumor, 5 fields with different density of CD68 were counted under 400x by optical microscopy and the average of the five fields was taken as the percentage. Patients were divided into the two groups of low infiltration and high infiltration based on the percentage of CD68.By the same way, patients were divided into the two groups of low infiltration and high infiltration based on Ki67 percentage. Results: CD68 positive cells had significant correlation with ER negative and higher Ki67. No significant correlation was found between CD68 positive cells and the number of involved lymph nodes, age, size, HER2neu, PR, stage and grade. Conclusion: It seems that the presence of CD68 -positive macrophages in invasive breast cancers and nearby lymph nodes is associated with a worse prognosis.